A COMPREHENSIVE ANALYSIS OF ETHICAL AND LEGAL CONSIDERATIONS IN THE INTEGRATION OF SOCIAL SERVICES AND HEALTH ASSISTANCE IN PROFESSIONAL STANDARDS AND PATIENT RIGHTS - 1Thaiban Dhafer Al khadhrah, 2Mohammad Salem Mohammad Algshanin, Refan3Nasser Mubarak Almutlq, 4Hanan Faisal Rashid Alharbi, 5Mesfer Salem Bin Jaber Lsalumi, 6 Faleh Marzooq Jaber Alsaleh, 7Al-Hassan Hadi Saleh Lasloum, 8Mana Hamad Ali Al Mansour, (Chelonian Research Foundation, 2022)
In recent years, with the understanding that nursing includes more than just treatment, the need to coordinate healthcare has become more vital. In any case, this integration brings with it a number of ethical and legitimate issues that should be considered in terms of securing patient rights and guaranteeing equity. This article comprehensively surveys these challenges through a writing review, a methodological audit, an introduction to the topic, and an in-depth dialog. This ponder highlights challenges by highlighting clashes within the integration of well-being and social administrations and offers proposals for specialists and policymakers. Through these suggestions, partners can conduct ethical and lawful investigations to guarantee that quality care is conveyed reasonably and lawfully, proficient guidelines are maintained, and patient rights are respected. Keywords: ethical considerations, legal considerations, social services, health assistance, professional standards, patient rights.